Globalization and Loneliness (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the topic is due to the importance of comprehending the impact of the globalization process on a human personality, as well as understanding the inconsistency of this impact, and the search for ways out of the current situation, complemented by the indispensability of forming the modern worldview attitudes of personality development. The process of globalization leads to the social isolation of the individual and a worldview crisis; the global nature of the problem and its inclusivity are assigning the debated topic of loneliness in the framework of globalization to a number of important philosophical problems. The aim of the study is an attempt to overcome the loneliness of the individual in the context of globalization. The author undertakes to identify the key causes of human loneliness in the modern world and its consequences for the individual and civilization as a whole. To determine ways out of the current situation, the author uses a systematic analysis of approaches to the problem of loneliness in the context of globalization. As a result, the author identifies factors that contribute to the emergence of feelings of loneliness and isolation of the individual in the world of global information freedom and also highlights areas of activity that contribute to leveling this feeling and reducing the negative impact of globalization on the individual. The materials of the article are of practical value for the vision of the problem of globalization within the framework of philosophical discourse.